Review: Farmasi Sosial dan Administratif: Review: Social and Administrative Pharmacy - Saud, Anshar (Universitas Tadulako, 2019)
In the health care system, pharmaceutical care systems are one of the core components and pharmacists play a very important role. With the dynamic changes that occur in health services, diseases, communication and regulatory information technology, the roles and responsibilities of pharmacists are becoming increasingly important than before. Pharmacists are dedicated and in a strategic position to maintain and advance public health. Their efforts improve the quality of life of individuals by helping people to live as freely as possible from illness, pain, and suffering. One of the obligations of pharmacists is to educate the public about health and drug use. Pharmacy practices involve pharmacists, patients, other professional health personnel and the public can be conceptualized as a social process. Therefore, understanding the concepts and principles behind social pharmacy disciplines is very essential and useful for a pharmacist and pharmacy student. The purpose of this article review is to briefly review a number of important topics concerning social, behavioral and administrative aspects in pharmacy to achieve a stronger understanding of dynamic and complex interactions between patients, pharmacists, drugs, teams of health workers, organizations and larger social systems. Mastery of students and pharmacists on this issue – asa consequence of the inclusion of social and administrative aspects into the pharmacy's higher education curriculum–willenable them to be professionally responsible for improving patient drug therapy outcomes as individuals, communities, society, and state systems; and have a greater impact on population health through drug-related public policies.